PENGARUH MODEL PEMBELAJARAN PROBLEM POSING TERHADAP HASIL BELAJAR DITINJAU DARI KEMAMPUAN AWAL SISWA KELAS VIII SMP NEGERI 4 MERANGIN - Rianti Junita; Hidayati Rais; Awatif (Hiradika | Hira Institute, 2024)
The aim of this research is to explain the learning outcomes of class VIII students at SMP Negeri 4 Merangin in the 2023/2024 academic year from the initial abilities taught using the problem position learning model which is better than conventional learning. By using experimental methods, this research uses a quantitative approach. This research involved a population of class VIII students and used a 2 by 3 factorial design. Simple random sampling is a sampling method. a method for collecting data through exams that use essay questions. The results of testing prerequisites for data analysis show that the data has a normal distribution and homogeneous variance. Therefore, to test hypotheses 1, 2, 3, and 4 is the t-test formula, and for hypothesis 5 is the two-way anova formula.. From the data analysis the final test, it was concluded that: learning outcomes using the Problem Posing learning model were no better or the same as conventional learning, learning outcomes with high initial abilities using the Problem Posing learning model were better than those of students with high initial abilities. low initial, medium and Problem Posing are more suitable for students with high initial abilities.